Sprawa kpt. Leona Stępnia (maj–grudzień 1949 r.). Przyczynek do historii ORMO w województwie olsztyńskim - Sacewicz, Karol (Komunizm: System - Ludzie - Dokumentacja, 2023)
The history of Volunteer Reserve of the Citizens’ Militia (Ochotnicza Rezerwa Milicji Obywatelskiej, ORMO), primarily its structures operating in Olsztyn Voivodeship, remains an area requiring scientific elaboration. The Volunteer Reserve of the Citizens’ Militia constituted the institutional and personal reinforcement of the communist power apparatus; it was often their tool against the democratic aspirations of Polish society. However, while there is a multitude of studies on the Security Service (Służba Bezpieczeństwa, SB) and Citizens’ Militia (Milicja Obywatelska, MO), scientific studies on ORMO remain scarce. Thus, the following article aims to discuss a small section of ORMO’s history in Warmia and Masuria that brings to focus all the features of the organization and the people creating it into focus. Captain Leon Stępień was ORMO’s commander of the Olsztyn Voivodeship. The article answers the questions of who he was and what offenses he was supposed to commit that not only the Executive of the Provincial Committee of the Polish United Workers’ Party in Olsztyn dealt with his case, but also the Central Committee of the Party, and the Central Command of the Citizens’ Militia. What is more, letters regarding this case were addressed directly to the Minister of Public Security, Stanisław Radkiewicz. What the so-called Stępień case constituted for the assessment of all the ORMO’s regional structures? Above all, how did the organization operate in that voivodeship? This article attempts at answering these questions and presenting mechanisms employed by the Party or ministerial leadership to “sweep the matter under the rug” and to ensure that its echoes did not reach the general public.